PENGARUH KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BPJS KETENAGAKERJAAN KANTOR WILAYAH JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA SERTA BPJS KETENAGAKERJAAN CABANG SEMARANG PEMUDA - Dwi Ayu Puspasari, 14.05.51.0210; Abdul Rozak, Hasan (Students' Journal of Economic and Management, 2018)
This study examines and analyzes the influence of leadership, motivation and work discipline on employee performance. This research was conducted at the BPJS Employment Office in Central Java and Yogyakarta Special Region and BPJS Employment Semarang Youth Branch. The population of this study is all employees of BPJS Employment in the Central Java Region and Yogyakarta Special Region and the BPJS Employment Semarang Branch of Youth which amounted 100 people by taking a sample using the census method. The method of analysis used in this study is to use regression analysis method, which uses the values of Standardized Beta Coeficients and Significant Levels. The result of the research shows that leadership has a positive and significant effect on employee performance, motivation does not significantly influence employee performance and work discipline has a positive and significant effect on employee performance. Keywords: Leadership, Motivation, Work Discipline and Employee Performance